Kepastian hukum pendaftaran hak atas tanah di Indonesia - Soerodjo, Irawan (Surabaya : Arkola, 2003)
Legal protection on registration and transfer of land titles in Indonesia.
Revision of the author's thesis (doctoral)--Universitas Airlangga, Surabaya, 1999.
"Undang-undang": p. 356-358.
Includes bibliographical references (p. 331-356).
Keywords: Land titles -- Registration and transfer -- Indonesia